Characterization of the Pank2-/- mouse retinal phenotype as a pre-clinical model for pantothenate kinase-associated neurodegeneration - Grace Li-Na Su; Suh Young Jeong; Dahlia Wafai; Wayne Tschetter; Dolly Zhen; Susan J. Hayflick; Renee C. Ryals (PLoS ONE, 2025)
Pantothenate kinase-associated neurodegeneration (PKAN) is an autosomal recessive movement and vision disorder in the neurodegeneration with brain iron accumulation family of diseases. PKAN is caused by mutations in PANK2, encoding pantothenate kinase 2, causing an inborn error of coenzyme A metabolism and leading to iron accumulation in the basal ganglia. Peripheral pigmentary retinopathy is common in people with PKAN. The knockout murine model of the orthologous Pank2 gene is known to manifest retinal degeneration through electroretinography, pupillary response and histology analyses. Our longitudinal characterization of the retinopathy in this model reveals reduced visual performance and reduced photoreceptor thickness compared to wild-type mice. Additionally, retinal perturbations in coenzyme A metabolism and dopamine metabolism pathways mimic those previously observed in the brain. These data extend the murine ocular phenotype associated with loss of function of Pank2. With a measurable behavioral, structural and mechanistic retinal phenotype, this mouse model is an ideal pre-clinical model that can be used to evaluate therapeutics for PKAN.